Resilience of Rural Communities During The Covid-19 Pandemic - Ernawati S. Kaseng (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
The study of this article aims to describe community resilience as a concept of community resilience in facing disasters; and the lives of rural communities during the Covid-19 pandemic; and the resilience of village communities during the Covid-19 pandemic. The method used in the study of this article is a literature study through secondary data that is collected and then compiled accordingly so that conclusions can be drawn. The conclusion from the results of the study, namely that the life of rural communities during the pandemic does not seem to be running as it is, such as houses of worship that are closed, associations are restricted, as well as children's educational activities are no longer carried out in schools but the learning process is carried out virtually. The Covid-19 pandemic, the economic sector of rural communities also seems to be not running normally due to limited community mobility and the rules applied in the community so that the harvests of village communities/farmers and fishermen cannot be sold directly to industries in the provincial capital as usual in normal times. It can be seen that collective action is able to build resilience in the community at the community level when facing the Covid-19 pandemic.